ANALISIS MODEL PENGARUH GOAL ORIENTATION, GENERAL SELF-EFFICACY DAN JENIS KELAMIN TERHADAP SELF-REGULATED LEARNING DALAM PEMBELAJARAN JARAK JAUH - Yudhistira, Santi; Deasyanti, Deasyanti; Muzdalifah, Fellianti (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Since COVID-19's entry into Indonesia in early March, 2020, the government has determined all educational institutions to carry out learning activities using the Distance Education method. The method changes are so fast that students as students who use this method do not have much time to adjust and meet various obstacles. This study aims to see how self-efficacy and goal orientation influences students self-regulated learning while carrying out distance education. This study also wants to look at differences in self-regulated learning between male and female students. This research uses quantitative methods. Respondents in this study were 319 students at a university in Jakarta who were carrying out learning activities with distance education methods. The instrument used is General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995), 2x2 Achievement Goal Orientation Framework (Elliot & McGregor, 2001), and Metacognitive Self-Regulation dalam Motivated Strategies Learning Questionaire (MSLQ). The validity of the measuring instrument was carried out using the Confirmatory Factor Analysis (CFA) method and hypothesis testing using path analysis processed through Mplus software version 7.11. The results of the path analysis test found that the model tested fit with the chi-square index = 2.39, df = 1, p-value = 0.25> 0.05), and RMSEA = 0.067. The final results of the study showed that self-efficacy, goal orientation, and gender had an effect of 19.7% on student self-regulated learning. Sejak masuknya COVID-19 ke Indonesia awal Maret tahun 2020, pemerintah menetapkan seluruh institusi pendidikan untuk melaksanakan kegiatan belajar dengan metode Pembelajaran Jarak Jauh (PJJ). Perubahan metode yang begitu cepat menyebabkan mahasiswa sebagai peserta didik yang menggunakan metode ini tidak memiliki banyak waktu untuk menyesuaikan diri dan menemui berbagai kendala. Penelitian ini bertujuan untuk melihat bagaimana pengaruh keyakinan diri (self-efficacy) dan penetapan tujuan belajar (goal orientation) terhadap strategi regulasi dan pengelolaan aktivitas belajar (self-regulated learning) pada mahasiswa dengan metode PJJ. Penelitian ini juga ingin melihat self-regulated learning pada mahasiswa laki-laki dan perempuan. Penelitian ini menggunakan metode kuantitatif. Responden dalam penelitian ini adalah 319 mahasiswa disalah satu universitas di Jakarta yang sedang melaksanakan kegiatan belajar dengan metode PJJ. Alat ukur yang digunakan yaitu General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995), 2x2 Achievement Goal Orientation Framework (Elliot & McGregor, 2001), dan Metacognitive Self-Regulation dalam Motivated Strategies Learning Questionaire (MSLQ). Validitas alat ukur dilakukan dengan metode Confirmatory Factor Analysis (CFA) dan pengujian hipotesis menggunakan Path Analysis yang diolah melalui software Mplus versi 7.11. Hasil uji Path Analysis diketehui model yang diuji fit dengan indeks chi-square=2,39, df=1, p-value=0,25 >0,05), dan RMSEA=0,067. Hasil akhir penelitian menunjukkan self-efficacy, goal orientation, dan jenis kelamin memberikan pengaruh sebesar 19,7% terhadap self-regulated learning pada mahasiswa.